2023
DOI: 10.1186/s12889-023-16378-0
|View full text |Cite
|
Sign up to set email alerts
|

Serial mediation of the relationship between impulsivity and suicidal ideation by depression and hopelessness in depressed patients

Xiaoli Chen,
Shupeng Li

Abstract: Background Close relationships have been observed among impulsivity, depression, hopelessness, and suicidal ideation in depressed patients. However, the precise mechanism that connects these psychological symptoms remains unclear. This study aims to explore the mediation effect of depression and hopelessness on the relationship between impulsivity and suicidal ideation in depressed patients. Methods A total of 258 depressed patients were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Impulsive individuals are more likely to overestimate the negative significance or underestimate the positive significance of things, manifesting overgeneralization, self-blame, rumination, etc., which are all related to depression [11]. It is therefore speculated that impulsive individuals are more prone to developing depression [12,13]. However, existing studies do not consistently support this view.…”
Section: Impulsivity and Adolescent Depressionmentioning
confidence: 99%
“…Impulsive individuals are more likely to overestimate the negative significance or underestimate the positive significance of things, manifesting overgeneralization, self-blame, rumination, etc., which are all related to depression [11]. It is therefore speculated that impulsive individuals are more prone to developing depression [12,13]. However, existing studies do not consistently support this view.…”
Section: Impulsivity and Adolescent Depressionmentioning
confidence: 99%
“…In recent years, the Epidemiological Research Center Depression Scale (CES-D) has been reported to have high detection rates in countries such as Italy (37%) and Spain (49%), which has prompted us to study psychiatric disorders in European countries ( 10 ). Early studies have found a strong association between depression and suicidal ideation ( 11 , 12 ), with approximately 58% of patients with major depressive episodes reporting suicidal thoughts ( 13 ), which suggests that the serious risk posed by psychiatric disorders to an individual’s health cannot be ignored. Recent studies have shown that current evidence does not support the hypothesis that depression is caused by reduced serotonin activity or concentration ( 14 ).…”
Section: Introductionmentioning
confidence: 99%